The role of transthoracal echocardiography in closing secundum atrial septal defects with Amplatzer Septal Occluder (Medical Journal of Indonesia, 2007)
Transesophageal echocardiography (TEE) under general anesthesia has become a routine procedure as guidance in implanting Amplatzer septal occluder (ASO) for closing secundum atrial septal defects (ASDs) together with fluoroscopy in cardiac catheterization laboratory. To simplify the procedure and reduce the cost, recently we used transthoracal echocardiography (TTE) in guiding the ASO implantation. Aim of this study is to evaluate accuracy and performance of ASO procedure guided by TTE compared to ASO procedure guided by TEE. This is a comparative study. Ninety-one patients with ASDs referred for transcatheter closure with ASO in National Cardiovascular Center Harapan Kita Hospital Jakarta were reviewed. In the 22 patients, TTE were used as guidance instead of TEE. Patients selection were performed in the outpatient clinic by TEE. The stretched diameter was measured by TEE or TTE and fluoroscopy. Patients were divided into two groups, TEE group consisted of procedures guided by TEE, and TTE group guided by TTE. From 91 patients, 83 can be evaluated. It consisted of 61 patients in TEE group and 22 in TTE group. Measurement of defects sizes with TTE and TEE have a high correlation with fluoroscopic measurements (r=0.837 and r=0.853, respectively). There were no significant differences between the accuracy of TTE and TEE sizes measurement (p=0.085) compared to fluoroscopy. Fluoroscopy time in ASO procedures guided by TEE was significantly longer than those guided by TTE (33.2 ± 21.3 min vs. 22.8 ± 19.3 min, P=0.014). There was also no significant differences in the failure of devices implantation between TEE and TTE guidance. All patients were in good condition at follow-up. ASO procedures guided by TTE have similar accuracy to those guided by TEE, with shorter fluoroscopy time. TTE guidance also has no difference in failure rate compared to TEE guidance. (Med J Indones 2007; 16:14-8) Keywords: amplatzer septal occluder, secundum atrial septal defect, transthoral echocardiography